Imaging a medieval shipwreck with the new PingPong 3D marine reflection seismic system. Issue 3 (20th March 2019) - Wilken, Dennis; Wunderlich, Tina; Hollmann, Hannes; Schwardt, Michaela; Rabbel, Wolfgang; Mohr, Clemens; Schulte‐Kortnack, Detlef; Nakoinz, Oliver; Enzmann, Jonas; Jürgens, Fritz; Wilkes, Feiko
Abstract: We present a new three‐dimensional (3D) marine seismic data acquisition system, named PingPong, developed for archaeological prospection in shallow water. Prospection targets for the system are ancient harbour sites and sedimented remains of shipwrecks. The prospection of such targets often means working at the transition from land to water, in areas of only a few meters of water depth and hardly accessible waters. An acquisition system for such environments needs to meet specific demands, especially low draught and marginal weight besides the requirements of archaeological prospection, meaning decimetre resolution and 3D imaging capabilities, together with fast multichannel acquisition to be able to cover large areas. We explain the properties of the PingPong system and show its imaging capabilities using the case study of a sedimented medieval shipwreck. The study area is located at the innermost part of the Baltic fjord Schlei, Germany. In 2014, divers found a wreck in this area, mostly covered by mud. Findings and two timbers, dated by dendrochronology, indicated that the wreck is a Scandinavian transport ship dating to the middle of the twelfth century and related to Schleswig, which is located 2 km northwest of the study area. We show that the PingPong system is able to image the major remains of the wooden wreck at the seafloor and underneath. The acquired seismic datacube has a resolution of 0.15 m. It shows a number of distinct reflections that can clearly be assigned to the shipwreck, helping to understand the overall condition of the wreck. The reflections originate from one half the ship's hull, which is tilted to the side. The reflections concentrate in the first metre below the seafloor and correlate well with the results from the diving prospection.